A system dynamics approach for modelling a lead-market-based export potential - Rainer Walz; Nicki Helfrich; Alexander Enzmann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2009)
For knowledge-intensive goods, foreign trade performance also depends on the quality of the technology. Important factors to consider are technological capa-bilities, various market factors which influence the chances of a country devel-oping a lead-market position, innovation-friendly regulation and the existence of internationally competitive complementary industry clusters. In order to model these aspects, various feedback mechanisms between these factors have to be taken into account, among them knowledge spillovers from the export success which lead to an erosion of a lead-market position over time. A system dynam-ics framework is used for a first implementation of a simulation model for wind energy technology exports from Germany. The empirical results show the ex-pected dynamics of the system and underline the importance of the various feedback loops.
urn:nbn:de:0011-n-1180673
Keywords: 330; Renewable energy technologies; exports; first-mover advantage; lead markets; Regenerative Energie; Technischer Fortschritt; Export; Windkraftanlage; Marktpotential; Deutschland